A bibliometric analysis of COVID-19 research published in nursing journals - Juyeon Oh; Aekyung Kim (Science Editing, 2020)
Purpose This bibliometric study investigated the current state of documents on coronavirus disease 2019 (COVID-19) published in nursing journals. The analysis focused on the description of most productive journals, institutions, and countries, as well as the characteristics of the documents. Methods The publications analyzed in this study were retrieved from the Web of Science database with search keywords. The searches used to establish the study dataset were last updated on July 10, 2020. The inclusion criteria were relevant English-language publications in journals published in the Science Citation Index Expanded or Social Science Citation Index. Content analysis of original articles and reviews was done. Results An analysis of 125 publications on COVID-19 from 48 journals showed that the most productive journal and country were the Journal of Clinical Nursing (n = 18) and the USA (n = 53), respectively. Original articles (n = 27, 21.6%) and review papers (n = 4, 3.2%) accounted for 24.8% of the articles, and the highest number of papers were found in early access (published ahead of print) (n = 51, 40.8%) and Q1 journals (n = 73, 58.4%). The content analysis found 10 data-based original articles or reviews, which dealt with the topics of nurse training (n = 2), nurses’ psychosocial status (n = 2), nursing research methodology (n = 1), nursing guidelines (n = 4), and protection for nurses (n = 1). Conclusion This study presents the current situation of nursing research on COVID-19 based on an analysis of publications in nursing journals and provides meaningful information to nursing researchers and editorial board members. The number of data-based original articles on nursing related to COVID-19 remains low.